Editorial - Stroud, Christopher; Williams, Quentin (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
This issue of Multilingual Margins presents two papers originally written more than 20 years ago and published as reports for the Swedish International Development Cooperation Agency (SIDA). In the mid-nineties, this organization held a healthy brief to improve education in so-called developing countries, especially focusing on early childhood education and adult literacies, and education for democracy and health. The Agency commissioned work on factors determining the successful or unsuccessful implementation of mother tongue/bilingual programs, and the two texts published in this special issue were written with a broad readership of educational aid workers, local politicians and policy makers in mind. Why republish this work (that was written for a relatively non-specialist audience) at this time for a predominantly academic readership?